SIMULASI NUMERIK UJI KEKUATAN TARIK ARAH TEGAK LURUS SERAT PADA STRUKTUR SILINDER BAMBU MENGGUNAKAN EXTENDED FINITE ELEMENT METHOD (XFEM) - Jody Timanta Sitepu, Martinus
Bamboo is a natural composite material. It is called a natural composite material because it’s consisted of fibers made of cellulose and the matrix is lignin. Cellulose acts as a reinforcing structure and increases the stiffness of bamboo. Mostly, bamboo is applied as a building structure and decoration. This is because there are still many properties of bamboo material that are not yet known. On this basis, so this research was carried out as a method to determine the mechanical properties of bamboo.